2016
DOI: 10.1186/s40001-016-0222-0
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation and clinical significance of cyclin-dependent kinase5 expression in cervical lesions: a clinical research study in Guangxi, China

Abstract: BackgroundStudies have been reported that cyclin-dependent kinase5 (CDK5) was associated with the development of several cancers. However, the relationship between CDK5 level and clinicopathological factors is still poorly understood in cervical diseases. The aim of the current study was to investigate the expression of CDK5 and its clinical significance in variant cervical lesions.MethodsImmunohistochemistry (IHC) was used to detect CDK5 expression in 54 cases of chronic cervicitis, 42 cases of condyloma acum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…Although CDK5 shares homologous structure with other CDKs, it is not cyclin-dependent and does not need to be phosphorylated in the T-loop for activation (66). CDK5 expression is upregulated in several types of cancer, and inhibition induces cancer cell death through a FOXO1-Bim pathway or mitochondrial dysfunction (67)(68)(69)(70)(71)(72)(73). Ehrlich et al (74) showed that expression of CDK5 was increased in HCC tissues, and was correlated with malignant phenotypes.…”
Section: Discussionmentioning
confidence: 99%
“…Although CDK5 shares homologous structure with other CDKs, it is not cyclin-dependent and does not need to be phosphorylated in the T-loop for activation (66). CDK5 expression is upregulated in several types of cancer, and inhibition induces cancer cell death through a FOXO1-Bim pathway or mitochondrial dysfunction (67)(68)(69)(70)(71)(72)(73). Ehrlich et al (74) showed that expression of CDK5 was increased in HCC tissues, and was correlated with malignant phenotypes.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies showed that aberrant expression of CDK5 had been observed in multiple human cancers, but not in normal tissues. CDK5 were positively correlated with lymph node metastasis and the stage of disease in head and neck squamous cell carcinoma, cervical lesions, lung cancer, hepatocellular carcinoma and nasopharyngeal carcinoma (5)(6)(7)(8)(9)(10), and its overexpression was also associated with the poor prognosis in colorectal cancer and breast cancer (7,8). Tumor tissues with high expression of cdK5 are usually insensitive to chemoradiotherapy and targeted therapy (11,12).…”
Section: Introductionmentioning
confidence: 99%